Temporal dynamics of soil salinization due to vertical and lateral saltwater intrusion at an onshore aquaculture farm - Yu, Xuan; Xu, Beiyuan; Yao, Rongjiang; Wei, Junhong; Tu, Tongbi; Chen, Zi (Agricultural water management, 2024)
Saltwater intrusion (SWI) on low-lying coastal farms causes soil salinization, which may gradually render the land unsuitable for cultivation. Many studies on SWI focus on groundwater flow and salt transport, where the temporal dynamic of consequent soil salinization is understudied. To understand the effects of SWI on soil salinity, we gathered multi-scale field datasets on water level and salinity during an aquaculture impoundment, which resulted in both vertical and lateral groundwater salinization. By comparing continuous field data before and after impoundment, we captured lateral SWI and vertical SWI processes and the resulting soil salinity variation. In the vertical SWI process, soils from the surface to 0.2 m-deep were salinized immediately after saltwater irrigation due to the downward hydraulic gradient. A relatively slow salinization was formed at a depth below 0.3 m. In the lateral SWI process, the hydraulic conductivity of the sediments was doubled, which resulted in a more significant variability of salinity. Our findings illustrate that the temporal agricultural water management associated with transforming cropland into aquaculture ponds can alter soil physical characteristics and hydrological conditions at different locations. The resulting soil salinization showed multi-scale variability, which was much more complex than groundwater salinization. Therefore, studying the complete transformation process of coastal land use can contribute to an improved understanding of soil and groundwater salinization due to agricultural activities, which is essential to protecting and managing coastal soils and the associated agroecosystem services. •Coastal impoundment causes vertical and lateral saltwater intrusion which can result in soil salinization.•Vertical saltwater intrusion increases topsoil salinity immediately after impoundment and salinizes deep soil slowly.•Lateral saltwater intrusion increases hydraulic head gradient and conductivity resulting in broad fresh-saline interface.